2018
DOI: 10.3892/ol.2018.9480
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑140‑5p suppresses cell proliferation and invasion in gastric cancer by targeting WNT1 in the WNT/β‑catenin signaling pathway

Abstract: MicroRNAs have been suggested as potential regulators in gastric cancer (GC) development through affecting the expression of their target genes. Previous studies have demonstrated that miR-140-5p is downregulated in GC. However, the underlying functional role of miR-140-5p in GC remains largely unknown. The present study revealed that miR-140-5p expression was significantly decreased in 60 GC tissues, compared with corresponding adjacent non-tumor tissues. A lower miR-140-5p expression was significantly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
(19 reference statements)
2
16
0
Order By: Relevance
“…One of the popular action mechanisms of lncRNAs is to serve as a competing endogenous RNA (ceRNA) to regulate the expression and function of target genes by binding and sequestering with miRNAs. 13 Among many miRNAs, miR-140-5p was selected as a candidate for further analysis since several publications have reported its tumor-suppressive role in GC, [14][15][16] and in this study, we confirmed that TMPO-AS1 negatively regulated miR-140-5p expression in GC cells, and the oncogenic effects of TMPO-AS1 overexpression on GC cells were partially reversed by miR-140-5p restoration. MiRNAs exert their functions by negative regulation of their target genes, 17 and this study further showed that miR-140-5p directly targets SOX4, a master mediator of EMT in GC cells.…”
Section: Discussionsupporting
confidence: 81%
“…One of the popular action mechanisms of lncRNAs is to serve as a competing endogenous RNA (ceRNA) to regulate the expression and function of target genes by binding and sequestering with miRNAs. 13 Among many miRNAs, miR-140-5p was selected as a candidate for further analysis since several publications have reported its tumor-suppressive role in GC, [14][15][16] and in this study, we confirmed that TMPO-AS1 negatively regulated miR-140-5p expression in GC cells, and the oncogenic effects of TMPO-AS1 overexpression on GC cells were partially reversed by miR-140-5p restoration. MiRNAs exert their functions by negative regulation of their target genes, 17 and this study further showed that miR-140-5p directly targets SOX4, a master mediator of EMT in GC cells.…”
Section: Discussionsupporting
confidence: 81%
“…Having shown that Wnt1 is a marker of adaptive immune tolerance in human LUAD, we sought to investigate its relevance to other types of cancers. We focused on colon, breast, hepatocellular, gastric and renal clear cell carcinomas, due to their reported associations with Wnt1 [24][25][26][27][28] . The abundance of CD8 + T cells can be measured by expression of the signature genes CD8a and CD8b 29 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, miR-140-5p inhibits invasion and migration of FaDu cells by targeting A disintegrin and metalloproteinase 10 in the Notch1 signaling pathway (28). miR-140-5p also inhibits gastric cancer by regulating the WNT1-mediated WNT/β-catenin signaling pathway (30).…”
Section: Introductionmentioning
confidence: 99%